2014
DOI: 10.1093/jhps/hnu006
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically assisted fixation of the lesser trochanter fracture: a case series

Abstract: Avulsion fractures of the lesser trochanter in adolescents are uncommon. This injury is a result of a sudden forceful contraction of the iliopsoas tendon. It usually occurs during vigorous sport activity. Historically, these injuries were treated non-operatively, with guarded results, including weak hip flexor strength and non-union, hindering return to competitive sport. We report a series of three arthroscopically assisted fracture fixations performed by the senior author, using cannulated screw fixation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…McKinney and collaborators have made a review of publications in English on the subject and, in none of them, surgical treatment was indicated [10]. We found in our research two authors indicating surgical treatment in cases whose evolution of conservative treatment has not been satisfactory [11][12][13].…”
Section: Literature Reviewmentioning
confidence: 72%
“…McKinney and collaborators have made a review of publications in English on the subject and, in none of them, surgical treatment was indicated [10]. We found in our research two authors indicating surgical treatment in cases whose evolution of conservative treatment has not been satisfactory [11][12][13].…”
Section: Literature Reviewmentioning
confidence: 72%
“…Conservative management with an anti-inflammatory medications and non-weight bearing for a period of 6 weeks, has been the most popular mode of treatment for the avulsion fractures of the lesser trochanter. Immobilization in a spica-cast has not been proved to be of an additional benefit in the conservative approach [3,5]. It has been suggested that surgical intervention should be considered with fragment displacement of greater than 2 cm or if early return to sports is indicated, but the fragment should be of sufficient size to hold hardware.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that surgical intervention should be considered with fragment displacement of greater than 2 cm or if early return to sports is indicated, but the fragment should be of sufficient size to hold hardware. According to the literature the complications of Conservative management are non-union and exostosis which will warrant a surgical intervention [3,4]. According to McKinney and Nelson based on the displacement, avulsion fractures of apophyses can be classified into four types.…”
Section: Discussionmentioning
confidence: 99%
“…3 Unfortunately, the literature on this injury and patient population is limited to only a few published case reports. 8,9,13,15,17,25 Regardless of the setting or mechanism of injury, lesser trochanter avulsion can produce significant morbidity. Severe pain, swelling, local tenderness to palpation, limited hip flexion, and disturbed gait and weightbearing are all symptoms of this injury and can inhibit daily function and return to competitive sports.…”
mentioning
confidence: 99%
“…Severe pain, swelling, local tenderness to palpation, limited hip flexion, and disturbed gait and weightbearing are all symptoms of this injury and can inhibit daily function and return to competitive sports. [8][9][10]12,13,15,17,20,25 Treatment is almost always nonoperative; to our knowledge, only 1 study has reported on the long-term results of nonoperatively treated patients, and that study included 5 patients. 20 While nonoperative treatment is preferred as the initial treatment option in most cases, McKinney et al 12 recommended surgical intervention for symptomatic nonunions and avulsions with a displacement greater than 2 cm.…”
mentioning
confidence: 99%